Resilient seed systems approach and methodology - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The participatory approach and methodology was field tested and implemented in a number of countries around the world with international and national partners. 2nd edition of resilient seed systems handbook was published in 2019, a training course was developed and delivered in Ethiopia for participants from East and Southern Africa.